Infuěncia do relevo na produtividade e custos do harvester - Simões, Danilo [UNESP]; Fenner, Paulo Torres [UNESP] (My University, 2010)
Among the several variables that influence timber harvesting is the slope, which influences the productivity of forest machines. In this experiment the harvester was evaluated technically and economically while cutting and processing eucalyptus activity on different slope classes. The technical analysis included a study of time and movements by the method of continuous time; productivity was determined by the volume in cubic meters of wood processing. The economic analysis included the parameters of operational cost, production cost and energy consumption. The analysis of the data showed that productivity decreased according to the increase of the percent slope inclination, resulting in an effective work hour productivity increase from 18.72 to 39.71 m 3sc, with a mean of operating cost of US$ 78.78 per work hour.
Infuence of relief in productivity and costs of harvester
Keywords: Forest mechanization; Times and movements; Variables; Continuous time; Different slopes; Energy consumption; Forest machines; Infuence; Operational costs; Production cost; Productivity increase; Several variables; Slope inclination; Technical analysis; Timber harvesting; Wood processing; Work hours; Costs; Cutting; Economic analysis; Harvesters; Logging (forestry); Machinery; Mechanization; Productivity; Cost benefit analysis; Economic Analysis; Forestry; Logging